SUCROSE ON IN VITRO ROOTING PHASE OF PAPAYA TREE ‘TAINUNG 01’ - SCHMILDT, Edilson Romais; AMARAL, José Augusto Teixeira do; SCHMILDT, Omar (Scientia Agraria, 2007)
Seminific propagation of the papaya tree has problems of spread of diseases and genetic variability due to the free pollination. The micropropagation seems to be an alternative for the production of seedlings with satisfactory quality and in great amount, starting from a single explant. With the objective of improve the techniques of propagation in vitro of papaya tree ‘Tainung 1’, generation F1, sucrose concentrations were assayed in the culture media, in the rooting phase, starting from the fourth subculture. Sprouts originating from of the fourth subculture, of 1.5 cm of length, containing 4 visible leaves with the naked eye, were submitted to five sucrose concentrations (0, 15, 30, 45 and 60 g L-1), in MS culture media, added of 0,2 mg L-1 of IBA. According to the obtained results the sucrose addition in the culture media, in concentrations varying from 15 to 30 g L-1, favors the in vitro rooting of papaya tree ‘Tainung 01’.